2020
DOI: 10.1021/acsbiomaterials.9b01897
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Formulated Graphene and Its Natural Rubber Nanocomposite Thin Film in Human Vaginal Epithelial Cells: An Influence of Noncovalent Interaction

Abstract: Graphene family materials (GFMs) are extensively explored for various biomedical applications due to their unique physical properties. The prime challenge is to establish a conclusive safety profile of these nanomaterials and their respective products or devices. Formulating GFMs with appropriate ingredients (e.g., surfactant/compatibilizer) will help to disperse them homogeneously (i.e., within the polymer matrix in the case of polymer–graphene nanocomposites) and aid in good interfacial interaction to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Graphene condoms are thinner than regular condoms. Due to the high strength of the graphene layer, it is possible to design a thinner condom [34,35]. This point causes the heat to be better directed, and couples experience more sexual pleasure in addition to ensuring pregnancy prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene condoms are thinner than regular condoms. Due to the high strength of the graphene layer, it is possible to design a thinner condom [34,35]. This point causes the heat to be better directed, and couples experience more sexual pleasure in addition to ensuring pregnancy prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, covalent interaction was used. Sukumar et al [34] showed that the functionalization of graphene with the right ingredients (e.g., surfactant/compatibilizer) could increase its dispersion and aid in good interfacial interaction to achieve the desired properties. This point is not excluded from using graphene in the design of condoms.…”
Section: Discussionmentioning
confidence: 99%
“…The biocompatibility test reveals that the nanocomposite with undiluted graphene causes acute toxicity to the cell, whereas the nanocomposite with diluted graphene has no toxic effects. 78 This might be due to the reduction in direct contact with the cell in the low graphene-loading nanocomposite. The skin irritation and sensitization test show no significant damage indicating that the graphene nanocomposite can be used for healthcare products such as a catheters, condoms, and gloves.…”
Section: Graphene Materials and Their Hybrids' Application In Various...mentioning
confidence: 99%
“…In addition, recent cytotoxicity study (conducted via both in vitro and in vivo) on G-WBEC utilising FLG/Natural rubber (FLG-C-NR) nanocomposite revealed that graphene incorporation within the NR matrix do not compromise its biocompatibility, as no sign of toxicity, nor skin irritation were observed for up to 48 hours exposure [188]. However, majority of the available literature results suggests that graphene toxicity (as well as its susceptible environmental effects) is largely attributable to the overall nature of the surface chemistry (functionalised sites, especially the reactive oxygen species dominant in the derivatives such as GO), particle size, number of layers, concentration of the graphene material [189], [190] and the processing techniques employed in the graphene production [180].…”
Section: Toxicity and Environmental Impact Of Graphene Materialsmentioning
confidence: 99%